2007
DOI: 10.1016/j.aim.2006.12.005
|View full text |Cite
|
Sign up to set email alerts
|

A k-tableau characterization of k-Schur functions

Abstract: We study k-Schur functions characterized by k-tableaux, proving combinatorial properties such as a k-Pieri rule and a k-conjugation. This new approach relies on developing the theory of k-tableaux, and includes the introduction of a weight-permuting involution on these tableaux that generalizes the Bender-Knuth involution. This work lays the groundwork needed to prove that the set of k-Schur Littlewood-Richardson coefficients contains the 3-point Gromov-Witten invariants; structure constants for the quantum co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
134
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(137 citation statements)
references
References 24 publications
0
134
0
Order By: Relevance
“…For G = SL n (C), Lam [15] identified the Schubert basis of H * (Gr SLn(C) ) with symmetric functions, called k-Schur functions, of Lapointe, Lascoux and Morse [18]; these arose in the study of Macdonald polynomials. The Schubert basis of H * (Gr SLn(C) ) are the dual k-Schur functions [19] which are generalized by the affine Stanley symmetric functions [14]. In [16] Pieri rules were given for the multiplication of Bott's generators on the Schubert bases of Bott's realization of H * (Gr SLn(C) ) and H * (Gr SLn(C) ).…”
Section: 2mentioning
confidence: 99%
“…For G = SL n (C), Lam [15] identified the Schubert basis of H * (Gr SLn(C) ) with symmetric functions, called k-Schur functions, of Lapointe, Lascoux and Morse [18]; these arose in the study of Macdonald polynomials. The Schubert basis of H * (Gr SLn(C) ) are the dual k-Schur functions [19] which are generalized by the affine Stanley symmetric functions [14]. In [16] Pieri rules were given for the multiplication of Bott's generators on the Schubert bases of Bott's realization of H * (Gr SLn(C) ) and H * (Gr SLn(C) ).…”
Section: 2mentioning
confidence: 99%
“…The k-Schur function s (k) λ (X; t) is the weighted generating function of starred strong tableaux of shape ρ(λ), where ρ is the bijection between k-bounded partitions and k + 1-cores introduced in [22]. In was also shown that the rank of ρ(λ) in the n-core poset equals |λ| and it is conjectured that the leading term of s (k) λ (X; t) in the Schur function expansion is s λ (X).…”
Section: Quasisymmetric Expansionmentioning
confidence: 99%
“…Recently, an alternative definition for k-Schur functions was given by Lam, Lapointe, Morse, and Shimozono [17] as the weighted generating function of starred strong tableaux which correspond with labeled saturated chains in the Bruhat order on the affine symmetric group modulo the symmetric group. This definition has been shown to correspond to the Schubert basis for the affine Grassmannian of type A [15] and at t = 1 it is equivalent to the k-tableaux characterization of Lapointe and Morse [22]. In this paper, we extend Haiman's dual equivalence relation on standard Young tableaux [12] to all starred strong tableaux.…”
mentioning
confidence: 99%
See 2 more Smart Citations